RugbySmart: Challenges and lessons from the implementation of a nationwide sports injury prevention partnership programme - Quarrie, K.; Gianotti, S.; Murphy, I.; Harold, P.; Salmon, D.; Harawira , J. (Sports Medicine, 2020)
In New Zealand, rugby is the cause of the greatest number and cost of sports injuries for people aged 5-40 years. Since 2000, New Zealand Rugby and the Accident Compensation Corporation (ACC) have partnered to develop and deliver a nationwide rugby-specific injury prevention programme, `RugbySmart`, which is a platform for the delivery of injury prevention messages. RugbySmart has focussed on primary and secondary prevention—preventing injuries from occurring, and minimising the severity of those injuries that do occur [1].